Cleaning of the seafood - Mumbai Archive Project Team (Jio Institute, 2024)
Cleaning seafood thoroughly before cooking is essential for food safety, hygiene, and quality control. Washing seafood separately from other ingredients and utensils reduces the risk of spreading harmful bacteria or pathogens to other foods and minimizes the likelihood of foodborne illness.